Knowledge of Biosafety Measures among Laboratory Personnel at Tertiary Level Public Hospitals in Dhaka City (Bangladesh Journal of Infectious Diseases, 2021)
Background: Biosafety is the principles, technologies and practices that are implemented to prevent the unintentional exposure to pathogens and toxins.Objective: The purpose of the present study was to assess the Status of biosafety safety measures practice by medical laboratory workers in public hospitals of Dhaka city.Methodology: This descriptive cross-sectional study was conducted with Data from Medical Laboratory Workers of Tertiary Level Public Hospitals of Dhaka City using a Semi-Structured Questionnaire. The study was conducted from May 2015 to November 2015. It was designed to assess the Status of Practicing Biosafety Safety Measures in Tertiary Level Public Hospitals of Dhaka City. The knowledge, training, level of education on Biosafety were assessed by medical laboratory workers.Result: The Data of this study is obtained from a total of 238 respondents. In this study it is observed that 224(94%) respondents could not say the concept of Biosafety as defined by WHO. In this study 118(49%) respondents do not know about biosafety cabinet and 84(35%) could say up to Biosafety Level IV and 36(15%) can say up to Biosafety Level 3. Orientation with biosafety tools is observed in 138(58%) respondents, 76(32%) got training during course and 78(33%) got training during service.Conclusion: In conclusion knowledge and training on biosafety of the laboratory worker are inadequate.Bangladesh Journal of Infectious Diseases 2020;7(2):49-56